PARTISIPASI MASYARAKAT DALAM PROGRAM PEMBANGUNAN KAMPUNG DI DISTRIK ABENAHO KABUPATEN YALIMO - Moke Wilil; Nur Aedah (JURNAL KEBIJAKAN PUBLIK, 2022)
This study aims to analyze and determine Community Participation in Village Development Programs in Abenaho District, Yalimo Regency, as well as analyze the supporting and inhibiting factors of community participation in village development in Abenaho District, Yalimo Regency. This study uses a qualitative descriptive approach conducted in Abenaho District, Yalimo Regency, the determination of informants is carried out by snowball. Data collection techniques used are observation and interviews. Data analysis includes the stages of data reduction, data presentation, and conclusion. The results showed that the form of community participation in village development in Abenaho District, Yalimo Regency, the form of community participation contributing to the village development program was starting from the delegation of authority stage, the community had the authority to participate in determining the priority of development programs in their village through musrembang, and the results of the musrembang proposed as a priority development program. Then in the partnership stage, the community partners with providers of tools and materials needed to carry out development programs. Then the stage, community consultation consults with village assistants regarding the development program they have launched and the reporting and accountability mechanisms. Then the information stage is disseminated effectively so that the community knows information about the development program in their village. Then it is related to the form of community participation in the form of delivering voices to fight for their rights and the open access provided. Supporting factors are the existence of social solidarity, responsibility, and intense information dissemination. Then the inhibiting factor is the misunderstanding factor and mutual suspicion from the community.